Pemberdayaan Kader Dalam Memanfaatkan Media Pembelajaran Audio Visual Guna Meningkatkan Pengetahuan dan Keterampilan Melakukan Effleurage Massage Untuk Mengurangi Keluhan Nyeri Punggung pada Ibu Hamil (Genitri: Jurnal Pengabdian Masyarakat Bidang Kesehatan, 2025)
The complaints of back pain in pregnant women in the second to third trimester is a complaints that always occurs in every pregnancy. Therefore, midwifery care management must be considered to reduce complaints of back pain in mothers so that the pregnancy is comfortable and the mothers can remain productive throughout the pregnancy. To overcome back pain during pregnancy, it is necessary to carry out massage therapy that is appropriate to the mother's condition, one of which is Effleurage Massage. The results of a preliminary survey from 33 cadres in Rw.04 Wonokromo Subdistrict, Surabaya, almost all of them, namely 25 cadres (75,8%) did not know about Effleurage Massage which can be done to reduce or overcome back pain in pregnant women, and for 8 cadres ( 24,2%) had known about Effleurage Massage but had never practiced the movements. The solution in this community service is to provide health education about complaints of back pain during Massage with a lecture method using leaflets as a medium of supportand encouragement. This community service aims to increase the knowledge and skills of cadres and pregnant women. The pregnancy and how to overcome them with Effleurage method used in this community service is to provide Health Education through lecture methods assisted by leaflets and impressive media. In this activity, pre-tests and post-tests were also carried out using questionnaires to determine the level of knowledge of cadres and pregnant women before and after being given health education. The results obtained from this activity were an increase in the knowledge and skills of cadres and pregnant women after being given Health Education about complaints of back pain during pregnancy and Effleurage Massage.
Keywords: Public Services; Effleurage Massage; Back Pain in Pregnancy